Towards a paradigm shift in water network design - Roberto del Teso March; Enrique Cabrera Marcet; Elena Gómez Sellés; Elvira Estruch Juan (Ingeniería del Agua)
Pressurized water transport has a highly energy consumption and must be reduced to mitigate Climate Change impacts. This energy reduction can be achieved by optimizing the process: reducing the volume of water to be transported (managing water demand and reducing water losses), and adjusting pressure with an eco-layout. This work compares the traditional water distribution design (the objective of the current method, prevailing for more than one century, is to minimize the investment and to guarantee the supply), with an eco-layout, whose objective is to prioritize efficiency, adjusting the pressure as much as possible to the service needs. This is an alternative and logic approach in a new framework: Safer electrical networks, reliable electromechanics’ equipment and the imperative need to reduce energy consumption. The eco-layout is more convenient from an environmental point of view and, besides, it is more economic, if all expenses are considered.